2015
DOI: 10.3390/su7089773
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Phase Change Materials on Compressed Air Expansion in CAES Plants

Abstract: Abstract:The integration of renewable energy in the electrical grid is challenging due to the intermittent and non-programmable generated electric power and to the transmission of peak power levels. Several energy storage technologies have been studied to find a solution to these issues. In particular, compressed air energy storage (CAES) plants work by pumping and storing air into a vessel or in an underground cavern; then when energy is needed, the pressurized air is expanded in an expansion turbine. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…CO 2 is converted to methanol in the temperature range of 250-300 • C and pressure range of 5-10 MPa using CuO/ZnO/Al 2 O 3 as a catalyst. The produced methanol CH 3 OH is liquid at ambient temperature and can be safely stored and handled.…”
Section: Methanol Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 is converted to methanol in the temperature range of 250-300 • C and pressure range of 5-10 MPa using CuO/ZnO/Al 2 O 3 as a catalyst. The produced methanol CH 3 OH is liquid at ambient temperature and can be safely stored and handled.…”
Section: Methanol Productionmentioning
confidence: 99%
“…Energy storage solutions are being implemented to compensate for the fluctuations in intermittent energy production [2]. Recent investigations indicate that the introduction of energy storage technologies [3,4] and routes can help to stabilize power output while also enhancing the reliability of renewable energy production [5].…”
Section: Introductionmentioning
confidence: 99%
“…Only one study proposed an economic modelling [17]. CAES was taken into account in the feasibility study for building energy retrofitting, [18] but the constraints due to architectural values and a lack of space caused it to be forgotten by many historic building refurbishment interventions [19]. Moreover, the debate between restoration professionals and energy engineers delayed the introduction of innovative solutions [20] and favored conventional approaches such as internal insulations or PV array installations on roofs [21].…”
Section: Introductionmentioning
confidence: 99%
“…So, the real interaction between device behaviour and load profile can be evaluated along with a more coherent integration strategy. Moreover, taking into account the development of CAES solutions at the small scale [16,18], the suitable source of renewable energy was selected, i.e., a PV array. This latter contributed to the electrification of rural areas [27] or towards the scenario of off-grid buildings that constitute self-sufficient districts and cities.…”
Section: Introductionmentioning
confidence: 99%
“…Since latent energy of phase-change transitions is much higher than specific heat capacity, PCM storage has the potential for much higher energy storage density than sensible TES. It has to be observed that PCMs can be used also for mechanical energy systems or for buildings [9,10]. Another key advantage of latent storage is that the phase transition is a quasi-isothermal process, a feature that facilitates TES integration and control within the ORC plant.…”
Section: Introductionmentioning
confidence: 99%